Halitosis and its Psychosocial Effects Among Patients Reporting at Dental out Patients Department: A Neglected Oral Health Issue in Pakistan - Ghulam Ali Siyal, Muhammad Ilyas Siddiqui, Kanwal Naz Ariser, Rafaina Shah, Muhammad Adil, Muhammad Najeeb6, Rehmatullah Kandhro, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To assess the burden of halitosis among dental patients and to explore the psychosocial factors associated with halitosis at Liaquat University Hospital, Hyderabad. Study Design: Cross sectional study Study Setting & Duration: was conducted at Dental OPD of Liaquat University Hospital Hyderabad from March to August 2017. Patients presented with halitosis at Dental OPD of Liaquat University Hospital Hyderabad via convenient sampling technique were selected within duration of six months. Methodology: A group of 239 subjects were included in this study and the simple convenient sampling technique was used to obtain data for the research. Written consent form was taken from each subject. Results: Among 239 participants, 115 were male and 124 were female. 81.59% of patients reported experience of bad breath.62.50% of individuals claimed that having bad breath had made them less social, 65% of respondents said they feared social interaction and public events. Conclusion: The most of participants of the study had halitosis, whether it was real or imagined, and it had an effect on the patients' social and marital lives and produces psychiatric symptoms such as stress, lack of confidence, isolation and avoidance of gathering. Keywords: Halitosis, Socialization, Emotional distress, Self-confidence